2020
DOI: 10.30934/kusbed.603335
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Absorbed Radiation Dose Levels of Lenses Thyroid and Oral Mucosa in Computed Tomography Imagining: Phantom Study

Abstract: Baş ve boyun bilgisayarlı tomografi (BT) görüntülemesi, en sık kullanılan radyolojik incelemelerinden biridir. Birçok hastalığın tanısında önemli rol oynar. Lens ve tiroid bezi radyasyona karşı en duyarlı organlardandır. Bu çalışmanın amacı, BT görüntülemesi yapıl an hastaların, lens, oral mukoza ve tiroid dokusunun maruz kaldığı radyasyon dozunun belirlenmesidir. Yöntem: Çalışmada, insan eşdeğeri olan Alderson Rando fantomunun tiroid, oral mukoza, lens bölgelerine termolüminesans dozimetreleri (TLD) yerleştir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…In the research, radiation doses affecting both superficial and deeper tissues of the oral cavity were meticulously measured, examining various exposure times ranging from 0.5 to 8 minutes, and thermoluminescence dosimeters (TLD-100) were used for precise measurement. According to the study of Günay et al [27], the radiation values measured for the oral mucosa during computed tomography were 10.36 mSv (minimum), 19.47 mSv (maximum) and the mean value was 15.15±2.96 mSv. According to the results of this study, the oral cavity internal mean value for 1 minute is 1.640925 mSv.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the research, radiation doses affecting both superficial and deeper tissues of the oral cavity were meticulously measured, examining various exposure times ranging from 0.5 to 8 minutes, and thermoluminescence dosimeters (TLD-100) were used for precise measurement. According to the study of Günay et al [27], the radiation values measured for the oral mucosa during computed tomography were 10.36 mSv (minimum), 19.47 mSv (maximum) and the mean value was 15.15±2.96 mSv. According to the results of this study, the oral cavity internal mean value for 1 minute is 1.640925 mSv.…”
Section: Resultsmentioning
confidence: 99%
“…When the data of Günay et al [27] and the data of this study are compared with each other, the radiation dose to which the patient is exposed during 1 CT scan and a 9.23-minute C-arm fluoroscopy scan is equal to each other. According to this comparison, it can be concluded that C-arm fluoroscopy has a minimal impact on the patient compared to CT.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…LiF:Mg,Ti material, chosen for its close equivalence to human tissue. This selection ensures accurate measurement of radiation exposure, as the material closely mimics human tissue properties [7].…”
Section: Methodsmentioning
confidence: 99%